What type of rainforest burnt in the South East Queensland's 2019/20 bushfires and how might this impact biodiversity. (7th March 2023) - Thorley, James; Srivastava, Sanjeev Kumar; Shapcott, Alison
Abstract: Bushfires burnt over 18 million hectares across Australia's east coast, including rainforests, over the spring and summer 2019/2020 period. Rainforest harbours a large percentage of Australia's biodiversity and does not usually burn and therefore understanding the extent and biodiversity implications was a priority. The National Indicative Aggregated Fire Extent Dataset (NIAFED) combined with detailed regional ecosystem (RE) mapping was used to estimate the perimeter and area of each of the burnt rainforest types within South East Queensland (SEQ). Previous biodiversity estimates for each rainforest regional ecosystem type combined with remnant ecosystem mapping data then enabled an assessment of the potential biodiversity impacts of the fires for SEQ rainforest. We found that 12% of the rainforest estate in SEQ was within the burn footprint (29 031 ha) including parts of the UNESCO World Heritage Gondwana Rainforests of Australia. Fifty per cent of the total remnant area of the Endangered rainforest type, semi‐evergreen vine thicket on Mesozoic to Proterozoic igneous rocks (RE: 12.12.17) was potentially burnt. This rainforest type has high diversity. Burn severity analysis found that the rainforest primarily burnt with low severity, however, there were patches of high severity. Accuracy assessment of severity mapping resulted in a weak correlation (0.57) due to the underestimation of ground fires in rainforest. As expected, we found rainforest‐suppressed fires. However, in contrast to expectations, we found the wettest rainforest types and putative past refugia burnt more than other rainforest types. These results suggest that given drought conditions any rainforest could burn, and we can expect that the area of rainforest will contract if both incidences of drought and wildfires increase due to climate change. Abstract : Abbreviated abstract summarizing the article: We found 12% of SE QLD rainforest was potentially burnt in the 2019/20 bushfires fortunately most burnt at low severity but some burnt at with high severity. In contrast to expectations, we found the wettest rainforest types and putative past refugia burnt more than other rainforest types. These results suggest that given drought conditions any rainforest could burn.